1, 000 Futures: Testing Resiliency Using Plausible Future Headlines. (June 2016) - Gordon, Theodore J.
In planning, prospective policies are often subjected to "what if" resiliency tests. The question is asked: would intended decisions work as well if unanticipated events were to occur? This testing approach has two principal problems: there are psychological impediments to an unbiased choice of the test events and the inventory of events from which to choose test events is essentially unbounded. This article describes a database of about one thousand future headlines that help overcome both issues. The headlines in this database describe future events; they are randomly accessed to avoid bias in the selection of events for testing resiliency and the large number of forecasts, while not an "unbounded universe" covers a broad spectrum of possibilities. In addition, many other uses are possible, including improving foresight, finding new market and product opportunities, analyzing competitive differentials, and testing possible strategies for novelty.